2017
DOI: 10.1080/1461670x.2017.1279029
|View full text |Cite
|
Sign up to set email alerts
|

Journalism and the Islamic Worldview

Abstract: This paper looks at the extent to which journalistic culture in Muslim-majority countries is shaped by a distinctive Islamic worldview. We identified four principles of an Islamic perspective to journalism: truth and truth-telling (siddiq and haqq), pedagogy (tabligh), seeking the best for the public interest (maslahah), and moderation (wasatiyyah). A survey of working journalists in Africa (Egypt,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 41 publications
(55 reference statements)
1
11
0
1
Order By: Relevance
“…In line with Muchtar et al's [12] definition, this research surmised that the brand of Islamic journalism practiced by voa-islam.com and Republika reported the 2019 Indonesian presidential election in catering to the Muslim voters; akin to the ummat concept. The focus of reporting can be denominated to the objectification of political and societal issues, as forewarned by Arifuddin [13], but from a Muslim perspective that caters to the protection and promotion of Islamic interests.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In line with Muchtar et al's [12] definition, this research surmised that the brand of Islamic journalism practiced by voa-islam.com and Republika reported the 2019 Indonesian presidential election in catering to the Muslim voters; akin to the ummat concept. The focus of reporting can be denominated to the objectification of political and societal issues, as forewarned by Arifuddin [13], but from a Muslim perspective that caters to the protection and promotion of Islamic interests.…”
Section: Discussionsupporting
confidence: 63%
“…With that in mind, this research defines Islamic journalism simply as a brand of journalism that is guided not by West-oriented journalistic values. Instead, Islamic journalism is a school of thought in journalism that practices journalistic principles and produces journalistic content based on the Qur'an and the Sunnah [12].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially noteworthy when looking at Tunisia, which might be subsumed in the Western imaginary within the rubric of ‘the Muslim world’. While Muchtar et al (2017) found some evidence of an interventionist ‘Islamic perspective to journalism’ in their study of Muslim-majority countries, they also found that journalists’ roles were shaped more by the local political, economic, and socio-cultural context.…”
Section: Literature Reviewmentioning
confidence: 93%
“…The Islamic faith is based on the two primary sources: the Qur'an, which Muslims believe to be the direct word of God and the Sunnah, which includes the traditions, Islamic customs, and religious practices concerning the life example of the Prophet Muhammad (Abdullah & Nadvi, 2011;Muchtar, Hamada, Hanitzsch, Galal, Masduki, & Ullah, 2017). Both these main sources of Islamic worldview encourage using reason and rationality as a basic means to protect oneself from falsehood, inaccuracy, and evil doing (Muchtar et. al, 2017).…”
Section: Chapter 2 Theoretical Framework (Or Worldview)mentioning
confidence: 99%